Effect of curcumin on the expression of p53, transforming growth factor‐β, and inducible nitric oxide synthase in oral submucous fibrosis: A pilot study. Issue 4 (17th December 2016) - Gupta, Shikha; Ghosh, Sujoy; Gupta, Sunita; Sakhuja, Puja
Abstract: Aim: The purpose of the present study was to find out the expression of p53, transforming growth factor‐β TGF‐β), and inducible nitric oxide synthase (iNOS) in oral submucous fibrosis (OSMF), proteins implicated in its pathophysiology, as well as malignant transformation. We also sought to determine the effect of curcumin on the expression of these markers through immunohistochemistry. Methods: The expression of p53, TGF‐β, and iNOS was evaluated through immunohistochemistry in 28 patients with OSMF before and after treatment with curcumin. Expression was evaluated semiquantitatively using a four‐point scale based on the percentage of cells showing positive staining. Results: The expression of p53, TGF‐β, and iNOS in OSMF was found to be statistically significant ( P <.05). After therapy with curcumin, a decrease in the expression of p53, TGF‐β, and iNOS was seen in 25%, 32.1%, and 32.1% of the samples, respectively; however, the difference in pretreatment and post‐treatment expressions was not found to be statistically significant. Conclusion: The present finding suggest that curcumin could have an effect on the expression of p53, iNOS, and TGF‐β in OSMF, and thus, could prove to be an effective chemopreventive agent for its management. The increased expression of p53, TGF‐β, and iNOS in OSMF is suggestive of the role of these markers in its pathophysiology.